Artificial bubble cloud targets for underwater acoustic remote sensing - Hwang, P; Roy, R; Crum, L (American Meteorological Society, 1995)
This article describes a technique that uses polymer additives to suspend air bubbles to form stable artificial bubble clouds. The results presented include the range of polymer concentrations for an effective bubble suspension; the void fraction, bubble size distribution, and stability of the generated artificial bubble clouds; and the effects of polymer on the acoustic properties of the bubble clouds, especially the acoustic velocity. It is concluded that, for low-frequency applications (less than 1 kHz), polymer concentrations of less than 1% do not modify significantly the acoustic velocity of bubble clouds. The stability of the produced bubble clouds can be made to last from a few hours to days or even months depending on the polymer concentration and the bubble size. Because only a low polymer concentration and small void fraction (both less than 1%) are needed to generate effective scattering, the density of the produced bubble cloud target and its response to hydrostatic pressure are similar to those of the ambient sea water; thus, adjustment to quasi-neutral buoyancy is not difficult. These results suggest that underwater acoustic targets and quasi-neutrally buoyant tracers that are small but have large acoustic cross sections can be produced with artificial bubble clouds suspended and stabilized by polymers.